Classroom situations as contributors to language anxiety and the relationship between anxiety and learners’ self-perceived English proficiency in Finnish EFL classroom contexts - Virtanen, Tia (fi=Turun yliopisto|en=University of Turku|, 2018)
The purpose of the present MA thesis was to examine language anxiety in the context of English instruction in Finnish schools. The study was focussed on the relationship between learners’ self-perceived English proficiency and language anxiety, as well as the most anxiety-inducing and least anxiety-inducing classroom situations according to the judgements of the learners. The data for the present study were collected in Southwest Finland during the spring of 2017, and the subjects were second year students from two upper secondary schools and eighth grade pupils from one secondary school. Altogether there were 69 subjects, 54 upper secondary school students and 15 secondary school pupils. The subjects filled in a questionnaire where they were asked to evaluate their own language skills and respond to items concerning their experiences of language anxiety. Correlations between self-evaluations and language anxiety scores were calculated, and the analysis revealed a significant negative correlation in the results of the upper secondary school students. Correlations were also calculated between language anxiety and the subjects’ comparisons of themselves to their peers, and significant correlations were found in the results of both groups, indicating that anxious learners considered their peers to be better at English than they were. The analysis of the subjects’ judgements of the classroom situations showed that the most anxiety inducing situations involved speaking, exposure, unpreparedness and error-correction.